2021
DOI: 10.1371/journal.pone.0254171
|View full text |Cite
|
Sign up to set email alerts
|

Correlated color temperature and light intensity: Complementary features in non-visual light field

Abstract: An appropriate exposure to the light-dark cycle, with high irradiances during the day and darkness during the night is essential to keep our physiology on time. However, considering the increasing exposure to artificial light at night and its potential harmful effects on health (i.e. chronodisruption and associated health conditions), it is essential to understand the non-visual effects of light in humans. Melatonin suppression is considered the gold standard for nocturnal light effects, and the activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Following the bright light exposure protocol participants are exposed to dim light again to assess whether melatonin suppression is continuous even after acute bright light exposure. They reported that under both bright light settings melatonin suppression was higher than dim light settings and at the 5700K setting the suppression was slightly higher than 3000K setting [14]. In another study Nagare, Rea & Figueiro questioned whether the position and the colour of the light source would affect the melatonin suppression level.…”
Section: Effects Of Circadian Disruptions On Human Wellbeingmentioning
confidence: 97%
“…Following the bright light exposure protocol participants are exposed to dim light again to assess whether melatonin suppression is continuous even after acute bright light exposure. They reported that under both bright light settings melatonin suppression was higher than dim light settings and at the 5700K setting the suppression was slightly higher than 3000K setting [14]. In another study Nagare, Rea & Figueiro questioned whether the position and the colour of the light source would affect the melatonin suppression level.…”
Section: Effects Of Circadian Disruptions On Human Wellbeingmentioning
confidence: 97%
“…Light with a 1900 K color temperature containing a spectrum ranging from 500 to 650 nm of yellow–orange–red light (1900 K) in 40 individuals (18–25 yrs) induced significantly higher levels of melatonin compared to light exposure to color temperatures at 3000, 4000, and 6600 K [ 116 ]. However, differences were not observed between color temperatures at 3000 and 5700 K in 16 individuals (9 females; 23.8 ± 3.1 yrs) [ 117 ]. Glutamate secretion, which is indicative of cognitive ability, was also promoted by 1900 K after two hours of light exposure [ 116 ].…”
Section: Properties Of Light Affecting Metabolismmentioning
confidence: 99%